Hydrogeochemistry and Acidic Property of Submarine Groundwater Discharge Around Two Coral Islands in the Northern South China Sea - Lui, Hon-Kit; Liu, Min-Yun; Lin, Hsiu-Chin; Tseng, Hsiao-Chun; Liu, Li-Lian; Wang, Feng-Yu; Hou, Wei-Ping; Chang, Rae; Chen, Chen-Tung Arthur (Frontiers in Earth Science, 2021)
Submarine groundwater discharge (SGD) is an important source of nutrients in many coastal regions, yet little information is available on its carbonate chemistry and the controlling factors. This study examined the processes and factors controlling the hydrogeochemistry and the acidic property of the groundwaters and SGD of two isolated coral islands, Liuqiu Island (13 km off southwestern Taiwan) and Dongsha Island (located in the northern South China Sea, 420 km away from Liuqiu Island). Our results showed that the total alkalinity and dissolved inorganic carbon (DIC) of the fresh SGD were controlled mainly by the chemical weathering of carbonate minerals. Part of the DIC came from the organic matter decomposition or soil CO2, reducing the pH and CO32- concentration. Distributions of the carbonate chemistry and nutrients of the SGD were controlled mainly by physical mixing between the groundwater and the ambient seawater under the seabed, the so-called subterranean estuary. The Ca2+ released through weathering significantly increased the saturation state of aragonite or calcite, reducing the corrosiveness of the SGD on the carbonate rocks. This study is likely the first to examine the acidic property of SGD on the biogenic carbonate spine of sea urchin and pteropod shell. The spring water with similar carbonate chemistry of the freshwater SGD endmember from Liuqiu Island with the saturation state of aragonite of 0.97 caused observable dissolution on the spine of sea urchin and pteropod shell, yet the spine dissolved more readily. This was because the spine is made of high-Mg calcite, which has a higher solubility than aragonite or calcite. Such a result implies that some marine organisms with carbonate skeletons or shells containing high Mg:Ca ratio may suffer the impact of ocean acidification earlier. Although the SGD may contribute less than 10% of freshwater discharge by river to the coastal area, its impact on coastal biogeochemical cycles and ecosystems due to its acidic property and continual effect on the coast all year round deserves further investigation.